2020
DOI: 10.1021/acsami.0c10183
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-like Vanadium Oxygen Hydrate (VOH) Nanosheets Intercalated and Exfoliated by Polyaniline (PANI) for Aqueous Zinc-Ion Batteries (ZIBs)

Abstract: A new approach is employed to boost the electrochemical kinetics and stability of vanadium oxygen hydrate (VOH, V2O5·nH2O) employed for aqueous zinc-ion battery (ZIB) cathodes. The methodology is based on electrically conductive polyaniline (PANI) intercalated–exfoliated VOH, achieved by preintercalation of an aniline monomer and its in situ polymerization within the oxide interlayers. The resulting graphene-like PANI–VOH nanosheets possess a greatly boosted reaction-controlled contribution to the total charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
103
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(110 citation statements)
references
References 68 publications
7
103
0
Order By: Relevance
“…[ 51,52 ] However, these peaks have shifted and became weaker in the VOH@PANI nanowires due to the interactions between the VOH nanowires and PANI species. [ 44 ] Consequently, the above Raman results give supporting evidence for the successful synthesis of the VOH@PANI nanowires.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…[ 51,52 ] However, these peaks have shifted and became weaker in the VOH@PANI nanowires due to the interactions between the VOH nanowires and PANI species. [ 44 ] Consequently, the above Raman results give supporting evidence for the successful synthesis of the VOH@PANI nanowires.…”
Section: Resultssupporting
confidence: 58%
“…Whereas an additional 11.5% weight loss that occurred above 400 °C is assigned to the decomposition of PANI. [ 44 ] Therefore, the weight ratio of PANI in the VOH@PANI nanowires can be calculated to be around 11.5%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the aforementioned discussion, introducing water molecules and PANI between the layers of V 2 O 5 (PANI‐V 2 O 5 · n H 2 O) at the same time can further enhance the electrochemical performance by synergistically exerting their respective advantages. [ 49,50 ] However, water molecules and large molecular weight of PANI will occupy the zinc ion diffusion channels and structural water may cause the material to dissolve, so the impact of the amount of molecules on performance and structure needs further exploration.…”
Section: Challenges and Optimizationmentioning
confidence: 99%
“…also serve the purpose of the spacer between the two adjacent layers of vanadium oxide-based materials. [225][226][227][228][229] The in situ intercalation of PANI in between the layer of V 2 O 5 widen the interlayer spacing and block the electrostatic interaction between charge carrier Zn 2 + and the host material, favoring facile diffusion of Zn 2 + ion. The DFT analysis showed that the PANI intercalation causes the Fermi level to move towards the conduction band and facilitates the charge transfer.…”
Section: Metal Oxide-polymer Compositesmentioning
confidence: 99%